Pengaruh Harga Emas Dunia, Jumlah Uang Beredar, Inflasi, dan Zakat terhadap Indeks Saham Syariah Indonesia (ISSI) - Zulfahani; Marliyah; Yanti, Nursantri (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research aims to determine the long-term and short-term impact of world gold prices, money supply, inflation, and zakat on the Indonesian shariah stock indices (ISSI). The dependent variables applied in this study are the world's gold price, money supply, inflation, and zakat. By applying the vector error correction model (VECM) analysis method in the series, data was interpolated to monthly data for 2017-2021. Secondary data is the form of data applied in this study using the Eviews 10 program. This is due to several factors influencing the index that changes the Islamic capital market by representing Indonesian stocks. Based on the results of hypothesis testing, the concluding are accepted in the form of long-term relationships between world gold prices and money supply influence it. In the short term, each dependent variable does not affect the ISSI.